40 Hz Blue LED Relieves the Gamma Oscillations Changes Caused by Traumatic Brain Injury in Rat - Yang, Xiaoyu; Li, Xuepei; Yuan, Yikai; Sun, Tong; Yang, Jingguo; Deng, Bo; Yu, Hang; Gao, Anliang; Guan, Junwen (Frontiers in Neurology, 2022)
Abstract Background:Photobiomodulation (PBM) using low-level light-emitting diode (LED) can be rapidly applied in various neurological disorders safely and non-invasively. Materials & Methods:Forty-eight rats were involved in this study. The traumatic brain injury (TBI) model of rat was set up by a controlled cortical impact (CCI) injury. An 8-channel cortex electrodes EEG was fixed to two hemispheres, and gamma oscillations was extracted according to each electrode. 40hz blue LED stimulation was set at four points of the frontal and parietal regions for 60 s each, six times per day for one week. Modified Neurologic Severity Scores (mNSS) was used to evaluate the level of neurological function. Results:In right-side TBI model, the gamma oscillation decreased in electrodes Fp2, T4, C4, and O2; but significantly increased after one week of 40hz Blue LED intervention. In left-side TBI model, the gamma oscillation decreased in electrodes Fp1, T3, C3, and O1; and similarly increased after one week of 40hz Blue LED intervention. Both left and right side TBI rats performed significantly better in mNSS after 40hz Blue LED intervention. Conclusions:TBI cause the decrease of gamma oscillations in injury side brain of rats. And 40hz Blue LED therapy could relieves the gamma oscillations change caused by TBI and improve the prognosis of TBI.